GaAs heterojunction solar cell based on multifunctional N-GQD composite film and preparation method thereof
By using multifunctional N-GQD composite thin film as interface passivation and downconversion layer in GaAs heterojunction solar cells, the problems of narrow spectral response range and serious interface carrier recombination of GaAs heterojunction solar cells are solved, and the problem of narrow spectral response range and serious interface carrier recombination is achieved. Improve efficiency and simplify preparation process.
Patent Information
- Application Number
- CN202411656290.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-19
AI Technical Summary
GaAs heterojunction solar cells have narrow spectral response range, severe interfacial carrier recombination, and complex preparation process and high cost.
The multifunctional N-GQD composite film was used as the interface passivation and downconversion layer, and N-GQDs were prepared by hydrothermal reaction, and then GaAs heterojunction solar cells were prepared by spin coating and suction filtration.
It effectively broadens the spectral response range of GaAs solar cells, reduces interfacial carrier recombination, improves the efficiency of solar cells, simplifies the preparation process, and reduces costs.
Smart Images

Figure CN119486348A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of semiconductor material technology, and in particular to a GaAs heterojunction solar cell based on a multifunctional N-GQD composite film and a preparation method thereof. Background Art
[0002] In recent years, GaAs (Gallium Arsenide) solar cells have been widely used in the field of aerospace batteries due to their direct band gap, excellent photoelectric conversion efficiency and radiation resistance. According to the Shockley-Queisser model, the photoelectric conversion efficiency of a single-junction GaAs solar cell can reach 30%. However, GaAs has weak absorption in the ultraviolet region, resulting in a narrow spectral response range of GaAs heterojunction solar cells, affecting the photoelectric conversion efficiency, and serious interface carrier recombination of GaAs heterojunction solar cells.
[0003] Quantum dot materials have down-conversion characteristics and functions similar to the front surface field (FSF) layer in solar cells. They can absorb ultraviolet light and emit visible light with a longer wavelength, inhibiting the non-radiative recombination of carriers between device interfaces. Therefore, they have great potential in solar cells to broaden the spectral response range of solar cells and enhance light absorption. For example, application No. 202310762199.0 mentions a method for preparing a quantum dot light-conversion film that can improve the photoelectric conversion efficiency of silicon solar cells. The quantum dot down-conversion film is applied to silicon solar cells to improve the conversion efficiency of silicon solar cells. However, the quantum dot film is prepared using an ultrasonic atomization film system, which is costly and complex. Summary of the invention
[0004] The present application provides a method for preparing a multifunctional N-GQD composite film and a GaAs heterojunction solar cell to solve the problems existing in the related art. The technical solution is as follows:
[0005] In a first aspect, an embodiment of the present application provides a GaAs heterojunction solar cell based on a multifunctional N-GQD composite film, comprising a GaAs substrate, on which an N-GQDs interface passivation layer and a doped N-GQDs hole transport layer are sequentially provided.
[0006] In one embodiment, it also includes a back electrode on the back side of the GaAs substrate; an anti-reflection layer and a front electrode are sequentially arranged on the hole transport layer.
[0007] In one embodiment, the back electrode is an Au electrode, and the Au electrode film thickness is 100-120 nm.
[0008] In one embodiment, the material of the hole transport layer is carbon nanotube, Mxene, PEdot or graphene, or a combination of two or more thereof.
[0009] In one embodiment, the anti-reflection layer is one of WO3, MgF2, and MoO3 thin films.
[0010] In one embodiment, the anti-reflection layer has a thickness of 10-30 nm.
[0011] In one embodiment, the front electrode has a thickness of 100-120 nm.
[0012] In one embodiment, the material of the front electrode is silver, titanium, copper, nickel, platinum or indium tin oxide, or a combination of two or more thereof.
[0013] In a second aspect, the present application provides a method for preparing a GaAs heterojunction solar cell based on a multifunctional N-GQD composite film, comprising the following steps:
[0014] Step S1, evaporating a back electrode on the back of GaAs, forming an ohmic contact after annealing, and spin-coating a layer of N-GQDs solution on the front of the GaAs substrate and drying it naturally;
[0015] Step S2, preparing a hole transport layer film by suction filtration, transferring the hole transport layer film to the GaAs surface, spin coating the N-GQDs solution on the surface of the hole transport layer and drying it naturally;
[0016] Step S3, vapor-depositing an anti-reflection layer and a front electrode on the front side of the heterojunction obtained in step S2 to prepare a GaAs heterojunction solar cell based on the multifunctional N-GQD composite film.
[0017] In one embodiment, the N-GQDs solution is prepared by a method comprising the following steps:
[0018] The aqueous solution of urea and citric acid is subjected to a hydrothermal reaction treatment, and after the reaction solution is separated into solid and liquid, the liquid phase is freeze-dried to obtain the N-GQDs powder; and the powder is dissolved in water to obtain the N-GQDs solution.
[0019] In one embodiment, the mass ratio of urea to citric acid is (0.6-0.9):(0.5-1).
[0020] In one embodiment, the conditions of the hydrothermal reaction are: reaction temperature 150-180° C., reaction time 12-24 h.
[0021] In one embodiment, the solid-liquid separation process is: first filtering with filter paper, then centrifuging the filtrate, and finally dialysis.
[0022] In one embodiment, the pore size of the filter paper is 0.05-0.1 μm.
[0023] In one embodiment, the centrifugal treatment has a centrifugal speed of 6000-10000 rpm, a centrifugal time of 20-40 min, and a dialysis time of 1-3 days.
[0024] In one embodiment, in step S1, the annealing temperature is 300-330° C., and the annealing time is 10-30 seconds.
[0025] In one embodiment, the concentration of the N-GQDs solution is 0.05-0.5 mg / ml.
[0026] In one embodiment, the rotation speed of spin coating N-GQDs is 3000-5000 rpm, and the time is 30-60 s.
[0027] In one embodiment, in step S2: the transfer method is to stick the filter membrane obtained by filtering the hole transport layer material on the front side of GaAs and dry it at a drying temperature of 60 to 80°C.
[0028] In one embodiment, the concentration of the N-GQDs solution is 0.05-0.5 mg / ml; the rotation speed of the spin coating N-GQDs solution is 3000-5000 rpm, and the time is 30-60 s.
[0029] The advantages or beneficial effects of the above technical solution include at least:
[0030] The present application uses N-GQDs as an interface passivation and down-conversion multifunctional layer of GaAs heterojunction solar cells, which can effectively broaden the spectral response range of GaAs solar cells, reduce interface carrier recombination, and improve the efficiency of GaAs heterojunction solar cells.
[0031] The GaAs heterojunction solar cell based on the multifunctional N-GQD composite film of the present application is prepared by hydrothermal synthesis of N-GQDs using low-cost raw materials, and then prepared into an interface passivation layer of the heterojunction cell by simple spin coating, and a hole transport layer thin film is prepared by a filtration method, which is transferred to a GaAs substrate, and finally a layer of N-GQDs is spin coated on the surface thereof to prepare a solar cell. The preparation process is simple and has commercial application prospects. In addition, compared with GaAs solar cells that do not use quantum dots, the photoelectric conversion efficiency can be significantly improved.
[0032] The above summary is for illustrative purposes only and is not intended to be limiting in any way. In addition to the illustrative aspects, embodiments and features described above, further aspects, embodiments and features of the present application will be readily apparent by reference to the accompanying drawings and the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In the accompanying drawings, unless otherwise specified, the same reference numerals throughout the multiple drawings represent the same or similar parts or elements. These drawings are not necessarily drawn to scale. It should be understood that these drawings only depict some embodiments disclosed in the present application and should not be regarded as limiting the scope of the present application.
[0034] Figure 1 The GaAs heterojunction solar cell structure based on the multifunctional N-GQD composite film of Example 1 is shown in FIG. 1 , wherein from bottom to top are the back Au electrode, the GaAs substrate, the N-GQDs interface passivation layer, the doped N-GQDs hole transport layer, the anti-reflection layer (ARC) and the front Ag electrode;
[0035] Figure 2 The UV-visible absorption (Uv-vis) and PL spectra of N-GQDs obtained in Example 1;
[0036] Figure 3 The XRD pattern of N-GQDs obtained in Example 1;
[0037] Figure 4 This is the infrared spectrum (IR) of N-GQDs obtained in Example 1;
[0038] Figure 5 This is the XPS spectrum of N-GQDs obtained in Example 1;
[0039] Figure 6 TEM spectrum of N-GQDs obtained in Example 1;
[0040] Figure 7 The reflectivity spectra of the GaAs heterojunction solar cell based on the multifunctional N-GQD composite film of Example 1 and the comparative example;
[0041] Figure 8 PL spectra of GaAs heterojunction solar cells based on multifunctional N-GQD composite films in Example 1 and the comparative example;
[0042] Fig. 9 This is an IV curve test diagram of the GaAs heterojunction solar cell based on the multifunctional N-GQD composite film of Example 1 and the comparative example. DETAILED DESCRIPTION
[0043] In the following, only some exemplary embodiments are briefly described. As those skilled in the art will appreciate, the described embodiments may be modified in various ways without departing from the spirit or scope of the present application. Therefore, the drawings and descriptions are considered to be exemplary and non-restrictive in nature.
[0044] In order to overcome the problems of narrow spectral response range, serious interface carrier recombination and cost of the above-mentioned GaAs solar cells, an embodiment of the present application provides a GaAs heterojunction solar cell based on a multifunctional N-GQD composite film, including a GaAs substrate, on which an N-GQDs interface passivation layer and a doped N-GQDs hole transport layer are sequentially provided.
[0045] N-GQDs is the abbreviation of N-doped Graphene Quantum Dots. N-GQDs are used as the interface passivation and down-conversion multifunctional layer of GaAs heterojunction solar cells. Due to the down-conversion and interface passivation functions of quantum dots, the conversion efficiency of solar cells is significantly improved.
[0046] In one embodiment, the N-GQDs interface passivation layer is formed by coating the N-GQDs solution on the front of the GaAs substrate by spin coating and drying naturally. In this embodiment, the concentration of the N-GQDs solution is 0.05-0.5 mg / ml; the rotation speed of the spin coating N-GQDs is 3000-5000 rpm, and the time is 30-60 seconds.
[0047] In one embodiment, the N-GQDs solution is prepared by hydrothermal reaction of urea and citric acid. As one embodiment, the aqueous solution of urea and citric acid is subjected to hydrothermal reaction, the reaction solution is subjected to solid-liquid separation, and the liquid phase is freeze-dried to obtain the N-GQDs powder; and dissolved in water to obtain the N-GQDs solution.
[0048] In one embodiment, urea and citric acid are weighed and dissolved in deionized water and stirred, and the solution is transferred to a high-pressure reactor after dissolution; the high-pressure reactor is moved into an oven and reacted at a certain temperature, and the solution is taken out after the reaction is completed, and the precipitate is removed by filtration to leave the filtrate; the filtrate is centrifuged, and the supernatant is taken, and the obtained supernatant is dialyzed and freeze-dried to obtain N-GQDs powder, and finally the N-GQDs powder is weighed to prepare a solution of a certain concentration.
[0049] In one embodiment, the mass ratio of urea to citric acid is (0.6-0.9):(0.5-1).
[0050] In one embodiment, the conditions of the hydrothermal reaction are: reaction temperature 150-180° C., reaction time 12-24 h.
[0051] In one embodiment, the solid-liquid separation process is: first filtering with filter paper, and then centrifuging the filtrate.
[0052] In one embodiment, the pore size of the filter paper is 0.05-0.1 μm.
[0053] In one embodiment, the centrifugal treatment has a centrifugal speed of 6000-10000 rpm, a centrifugal time of 20-40 min, and a dialysis time of 1-3 days.
[0054] The N-GQDs are prepared with low-cost, non-toxic and environmentally friendly raw materials urea and citric acid, and the N-GQDs can be prepared by hydrothermal reaction, and the preparation process is simple. The N-GQDs interface passivation layer can be obtained by simple spin coating.
[0055] In one embodiment, the doping of the N-GQDs hole transport layer is to combine the N-GQDs solution with the hole transport layer by spin coating. In this embodiment, the concentration of the N-GQDs solution is 0.05-0.5 mg / ml; the rotation speed of the spin coating of the N-GQDs solution is 3000-5000 rpm, and the time is 30-60 seconds.
[0056] In one embodiment, the material of the hole transport layer is carbon nanotube, Mxene, PEdot or graphene, or a combination of two or more thereof.
[0057] In one embodiment, it also includes a back electrode on the back side of the GaAs substrate; an anti-reflection layer and a front electrode are sequentially arranged on the hole transport layer.
[0058] In one embodiment, the back electrode is an Au electrode, and the Au electrode film thickness is 100-120 nm.
[0059] In one embodiment, the anti-reflection layer is one of WO3, MgF2, and MoO3 thin films.
[0060] In one embodiment, the front electrode has a thickness of 100-120 nm.
[0061] In one embodiment, the material of the front electrode is silver, titanium, copper, nickel, platinum or indium tin oxide, or a combination of two or more thereof.
[0062] The present application embodiment provides a method for preparing a GaAs heterojunction solar cell based on a multifunctional N-GQD composite film, comprising the following steps:
[0063] Step S1, evaporating a back electrode on the back of GaAs, forming an ohmic contact after annealing, and spin-coating a layer of N-GQDs solution on the front of the GaAs substrate and drying it naturally;
[0064] Step S2, preparing a hole transport layer film by suction filtration, transferring the hole transport layer film to the GaAs surface, spin coating the N-GQDs solution on the surface of the hole transport layer and drying it naturally;
[0065] Step S3, vapor-depositing an anti-reflection layer and a front electrode on the front side of the heterojunction obtained in step S2 to prepare a GaAs heterojunction solar cell based on the multifunctional N-GQD composite film.
[0066] In one embodiment, the N-GQDs solution is prepared by a method comprising the following steps:
[0067] The aqueous solution of urea and citric acid is subjected to a hydrothermal reaction treatment, and after the reaction solution is separated into solid and liquid, the liquid phase is freeze-dried to obtain the N-GQDs powder; and the powder is dissolved in water to obtain the N-GQDs solution.
[0068] In one embodiment, the mass ratio of urea to citric acid is (0.6-0.9):(0.5-1). Urea and citric acid are dissolved in water to prepare an aqueous solution of urea and citric acid, wherein the mass volume ratio of citric acid to water is (0.5-1) g:(15-25) ml. In this embodiment, the aqueous solution is stirred at room temperature for 5-10 min.
[0069] In one embodiment, the conditions of the hydrothermal reaction are: reaction temperature 150-180° C., reaction time 12-24 h.
[0070] In one embodiment, the solid-liquid separation process is: first filtering with filter paper, and then centrifuging and dialyzing the filtrate.
[0071] In one embodiment, the pore size of the filter paper is 0.05-0.1 μm.
[0072] In one embodiment, the centrifugal treatment is carried out at a centrifugal speed of 6000 to 10000 rpm and a centrifugal time of 20 to 40 min.
[0073] In one embodiment, in step S1, the annealing temperature is 300-330° C., and the annealing time is 10-30 seconds.
[0074] In one embodiment, the concentration of the N-GQDs solution is 0.05-0.5 mg / ml.
[0075] In one embodiment, the rotation speed of spin coating N-GQDs is 3000-5000 rpm, and the time is 30-60 s.
[0076] In one embodiment, in step S2, the transfer method is to paste the filter membrane obtained by filtering the hole transport layer material on the front side of GaAs and dry it at a drying temperature of 60-80° C. GaAs heterojunction solar cells can be quickly prepared by simple filtration and transfer.
[0077] In one embodiment, the concentration of the N-GQDs solution is 0.05-0.5 mg / ml; the rotation speed of the spin coating N-GQDs solution is 3000-5000 rpm, and the time is 30-60 s.
[0078] The following is a further description with reference to specific embodiments.
[0079] Example 1
[0080] A GaAs heterojunction solar cell based on a multifunctional N-GQD composite film and a preparation method thereof, comprising the following steps:
[0081] Weigh 0.72g urea and 0.84g citric acid, add 18ml deionized water to dissolve, stir for 10min, transfer to a 50ml hydrothermal reactor at room temperature;
[0082] The autoclave was placed in a vacuum oven, the reaction temperature was 180°C, the reaction time was 24 h, after the reaction was completed, the solution was taken out, and filtered using a filter paper with a pore size of 0.1 μm to remove the precipitate and leave the filtrate;
[0083] The filtrate was centrifuged at 10000 rpm for 40 min, and the obtained supernatant was dialyzed for 3 days and freeze-dried for 72 h to obtain N-GQDs powder, and the obtained N-GQDs powder was prepared into an N-GQDs solution with a concentration of 0.1 mg / ml;
[0084] An Au electrode was evaporated on the back of GaAs, with an Au film thickness of 120 nm, an annealing temperature of 330°C, and an annealing time of 20 seconds to form an ohmic contact. N-GQDs were coated on the GaAs substrate by spin coating at a speed of 3000 rpm for 30 seconds. Then, carbon nanotubes were prepared into a filter membrane by suction filtration and pasted on the front of GaAs for drying at a drying temperature of 60°C. Then, 10 μl of the N-GQDs solution was spin-coated on the surface of the hole transport layer and dried naturally.
[0085] Ag electrode and WO3 were evaporated on the front side of the heterojunction. The thickness of WO3 was 30nm and the thickness of the electrode was 120nm to prepare a GaAs heterojunction solar cell based on a multifunctional N-GQD composite film. The structure is as follows: Figure 1 shown.
[0086] Example 2
[0087] A GaAs heterojunction solar cell based on a multifunctional N-GQD composite film and a preparation method thereof, comprising the following steps:
[0088] Weigh 0.6g urea and 1g citric acid, add 15ml deionized water to dissolve, stir for 5min, transfer to a 50ml hydrothermal reactor at room temperature;
[0089] The autoclave was placed in a vacuum oven, the reaction temperature was 150°C, the reaction time was 24 hours, after the reaction was completed, the solution was taken out, and filtered using a filter paper with a pore size of 0.05 μm to remove the precipitate and leave the filtrate;
[0090] The filtrate was centrifuged at 8000 rpm for 20 min, the obtained supernatant was dialyzed and freeze-dried for 24 h to obtain the N-GQDs powder, and the obtained N-GQDs powder was prepared into an N-GQDs solution with a concentration of 0.05 mg / ml;
[0091] An Au electrode was evaporated on the back of GaAs with a thickness of 100 nm. The annealing temperature was 315°C and the annealing time was 10 s to form an ohmic contact. N-GQDs were coated on the GaAs substrate by spin coating at a speed of 5000 rpm for 60 s. The carbon nanotubes were then prepared into a filter membrane by filtration and pasted on the front of GaAs for drying at 80°C. 20 μl of the N-GQDs solution was spin coated on the surface of the hole transport layer and allowed to dry naturally.
[0092] A Ni electrode and WO3 were evaporated on the front side of the heterojunction. The thickness of WO3 was 20 nm and the thickness of the electrode was 110 nm to prepare a GaAs heterojunction solar cell based on a multifunctional N-GQD composite film.
[0093] Example 3
[0094] A GaAs heterojunction solar cell based on a multifunctional N-GQD composite film and a preparation method thereof, comprising the following steps:
[0095] Weigh 0.9 g urea and 0.5 g citric acid, add 20 ml deionized water to dissolve, stir for 5 min, transfer to a 50 ml hydrothermal reactor at room temperature;
[0096] The autoclave was placed in a vacuum oven, the reaction temperature was 165°C, the reaction time was 12 h, after the reaction was completed, the solution was taken out, and filtered using a filter paper with a pore size of 0.1 μm to remove the precipitate and leave the filtrate;
[0097] The filtrate was centrifuged at 6000 rpm for 30 min, and the obtained supernatant was freeze-dried for 36 h to obtain the N-GQDs powder, and the obtained N-GQDs powder was configured into an N-GQDs solution with a concentration of 0.5 mg / ml;
[0098] An Au electrode was evaporated on the back of GaAs with a thickness of 110 nm. The annealing temperature was 300°C and the annealing time was 30 s to form an ohmic contact. N-GQDs were coated on the GaAs substrate by spin coating at a speed of 4000 rpm for 45 s. The carbon nanotubes were then prepared into a filter membrane by filtration and pasted on the front side of GaAs for drying at 70°C. 5 μl of the N-GQDs solution was drop-cast on the surface of the hole transport layer for natural drying.
[0099] Cu electrode and MoO3 were evaporated on the front side of the heterojunction. The thickness of MoO3 was 10nm and the thickness of the electrode was 100nm to prepare a GaAs heterojunction solar cell based on the multifunctional N-GQD composite film.
[0100] Comparative Example 1
[0101] Comparative Example 1 differs from Example 1 in that N-GQDs are not added as interface passivation and down-conversion functional layers, and a carbon nanotube dispersion containing the same mass of carbon nanotubes is filtered to prepare a thin film, which is then transferred to a GaAs substrate to prepare a carbon nanotube / GaAs heterojunction solar cell.
[0102] The N-GQDs prepared in the example were subjected to UV-visible absorption detection. The UV-visible absorption (Uv-vis) and PL spectra were shown in Figure 2. Figure 2 As shown;
[0103] The N-GQDs prepared in the example were subjected to X-ray diffraction detection, and the XRD spectrum was as follows: Figure 3 As shown;
[0104] The N-GQDs prepared in the example were subjected to infrared spectroscopy detection, and the infrared spectrum (IR) is shown as follows: Figure 4 As shown;
[0105] The N-GQDs prepared in the example were subjected to X-ray photoelectron spectroscopy detection, and the XPS spectrum was as follows Figure 5 As shown;
[0106] The N-GQDs prepared in the example were examined by transmission electron microscopy, and the TEM spectrum was as follows: Figure 6 As shown;
[0107] The reflectivity curves of the solar cells prepared in the embodiment and the solar cells prepared in the comparative example are as follows: Figure 7As shown;
[0108] The PL curves of the solar cells prepared in the embodiment and the solar cells prepared in the comparative example are as follows: Figure 8 As shown;
[0109] from Figure 2-6 It can be seen that the present application prepared N-GOD and N-GQD with a final average particle size of 3 to 5 nm, uniform particle size distribution and good dispersion, and good quality. Figure 7-8 It can be seen that after the introduction of N-GQDs, the reflectivity spectrum shows ( Figure 7 ), its reflectivity is significantly reduced, which means that more solar spectrum is absorbed, and it shows lower reflection in the ultraviolet band, which confirms that N-GQDs can absorb the ultraviolet spectrum. The PL spectra of the embodiment and the comparative example ( Figure 8 ) It can be seen that the strong PL peak in the comparative example indicates that there is serious carrier recombination in the GaAs solar cell. After inserting N-GQDs, the PL emission can be highly quenched, indicating that N-GQDs have a good passivation effect. In the examples of the present application, N-GQDs have been prepared using urea and citric acid, which can effectively broaden the spectral response range of GaAs solar cells, reduce interface carrier recombination, and improve the efficiency of solar cells.
[0110] The device parameters of the solar cell prepared in Example 1 and the solar cell prepared in Comparative Example 1 are shown in Table 1. The IV curve of the solar cell in Example 1 is shown in Fig. 9 As shown;
[0111] Table 1 Solar cell device parameters
[0112] Parameters / Samples Example 1 Comparative Example 1 <![CDATA[J sc (mA / cm 2 )]]> 29.8 23.01 PCE(%) 16.53 11.75
[0113] From Table 1 and Fig. 9 It can be seen that the short-circuit current density J of the solar cell of Example 1 of the present application is sc Reached 29.8mA / cm 2 , while in comparative example 1, N-GQD is not added as the interface passivation and down-conversion functional layer, and the short-circuit current density J sc Only 23.01mA / cm 2 From the perspective of energy conversion efficiency PCE, the PCE of the solar cell of Example 1 of the present application reaches 16.53%, while the PCE of the solar cell of Comparative Example 1 is only 11.75%. This indicates that the solar cell of Comparative Example 1 has a narrow spectral response range, serious carrier recombination, and low solar cell conversion efficiency compared to the GaAs heterojunction solar cell prepared by the preparation method of the present application.
[0114] In summary, the present application provides a GaAs heterojunction solar cell based on a multifunctional N-GQD composite film and a preparation method thereof, wherein N-GQDs are hydrothermally synthesized using low-cost raw materials, and then the interface passivation layer of the heterojunction battery is prepared by simple spin coating, and a hole transport layer thin film is prepared by a filtration method, which is transferred to a GaAs substrate, and finally a layer of N-GQDs is spin coated on the surface thereof to prepare a solar cell, which can effectively broaden the spectral response range of GaAs solar cells, reduce interface carrier recombination, and improve efficiency.
[0115] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine different embodiments or examples described in this specification and the features of different embodiments or examples, unless they are contradictory.
[0116] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0117] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of various changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A GaAs heterojunction solar cell based on a multifunctional N-GQD composite film, characterized in that: The invention comprises a GaAs substrate, on which an N-GQDs interface passivation layer and a doped N-GQDs hole transport layer are arranged in sequence.
2. A GaAs heterojunction solar cell based on a multifunctional N-GQD composite film according to claim 1, characterized in that: It also includes a back electrode on the back of the GaAs substrate; an anti-reflection layer and a front electrode are arranged in sequence on the hole transport layer.
3. A GaAs heterojunction solar cell based on a multifunctional N-GQD composite film according to claim 1 or 2, characterized in that: The back electrode is an Au electrode, and the Au electrode film thickness is 100-120 nm; The material of the hole transport layer is one or a combination of two or more of carbon nanotubes, Mxene, PEdot or graphene.
4. A GaAs heterojunction solar cell based on a multifunctional N-GQD composite film according to claim 3, characterized in that: The anti-reflection layer is one of WO3, MgF2, and MoO3 thin films; The thickness of the front electrode is 100-120 nm; the material of the front electrode is one or a combination of two or more of silver, titanium, copper, nickel, platinum or indium tin oxide.
5. A method for preparing a GaAs heterojunction solar cell based on a multifunctional N-GQD composite film, characterized in that: The following steps are involved: Step S1, evaporating a back electrode on the back of GaAs, forming an ohmic contact after annealing, and spin-coating a layer of N-GQDs solution on the front of the GaAs substrate and drying it naturally; Step S2, preparing a hole transport layer film by suction filtration, transferring the hole transport layer film to the GaAs surface, spin coating the N-GQDs solution on the surface of the hole transport layer and drying it naturally; Step S3, vapor-depositing an anti-reflection layer and a front electrode on the front side of the heterojunction obtained in step S2 to prepare a GaAs heterojunction solar cell based on the multifunctional N-GQD composite film.
6. The method for preparing a GaAs heterojunction solar cell based on a multifunctional N-GQD composite film according to claim 5, characterized in that: The N-GQDs solution is prepared by a method comprising the following steps: The aqueous solution of urea and citric acid is subjected to a hydrothermal reaction treatment, and after the reaction solution is separated into solid and liquid, the liquid phase is freeze-dried to obtain the N-GQDs powder; and the powder is dissolved in water to obtain the N-GQDs solution.
7. The method for preparing a GaAs heterojunction solar cell based on a multifunctional N-GQD composite film according to claim 6, characterized in that: The mass ratio of urea to citric acid is (0.6-0.9):(0.5-1); The conditions of the hydrothermal reaction are: reaction temperature 150-180°C, reaction time 12-24h.
8. The method for preparing a GaAs heterojunction solar cell based on a multifunctional N-GQD composite film according to claim 6, characterized in that: The solid-liquid separation process is: first filter with filter paper, then centrifuge the filtrate, and finally dialyze; the pore size of the filter paper is 0.05-0.1 μm; the centrifugal speed is 6000-10000 rpm, the centrifugal time is 20-40 minutes; the dialysis time is 1-3 days.
9. The method for preparing a GaAs heterojunction solar cell based on a multifunctional N-GQD composite film according to claim 5, characterized in that: In step S1: the annealing temperature is 300-330° C., and the annealing time is 10-30 seconds; The concentration of the N-GQDs solution is 0.05-0.5 mg / ml; the rotation speed of the spin coating N-GQDs is 3000-5000 rpm, and the time is 30-60 s.
10. The method for preparing a GaAs heterojunction solar cell based on a multifunctional N-GQD composite film according to claim 5, characterized in that: In step S2: the transfer method is to paste the filter membrane obtained by filtering the hole transport layer material on the front side of GaAs and dry it at a drying temperature of 60 to 80°C; The concentration of the N-GQDs solution is 0.05-0.5 mg / ml; the rotation speed of the spin coating N-GQDs solution is 3000-5000 rpm, and the time is 30-60 s.
Citation Information
Patent Citations
Preparation method of quantum dot light conversion film capable of improving photoelectric conversion efficiency of silicon solar cell
CN116682892A
Carbon nanotube / silver nanowire composite film, gallium arsenide-based heterojunction solar cell thereof and preparation method of gallium arsenide-based heterojunction solar cell
CN114823931A
Metal nitrogen-doped graphene quantum dot composite material, preparation method and application
CN115947340A
Hole transport material and gallium arsenide solar cell
CN116963569A
Fluorine-nitrogen co-doped graphene quantum dot as well as preparation method and application thereof
CN117247002A